Haul-out pattern of itinerant male Antarctic fur seals (Arctocephalus gazella) at Laurie Island, South Orkney Islands - Carlini, Alejandro R; Daneri, Gustavo A; Casaux, Ricardo; Márquez, María E I (Polar Research, 2006)
The seasonal haul-out pattern of itinerant male Antarctic fur seals (Arctocephalus gazella) was determined by regular counts at Mossman Peninsula, Laurie Island, South Orkney Islands, from 1996 to 2005. Small numbers of animals began to arrive at the beach in late December / early January (mean date 28 December ± 15 days, n = 10). Peak numbers of animals ashore changed considerably between seasons. In 1996, 1998 and 2001, peak numbers were registered in March (6/3, 18/3 and 6/3, respectively). Numbers peaked in 1997, 1999 and 2005 at the end of January / beginning of February (26/1, 2/2 and 28/1, respectively). In 2000, 2002, 2003 and 2004 peaks were registered in the third week of February (15/2, 22/2, 14/2 and 20/2, respectively). Peaks in numbers of seals ashore also varied between years, being minimum during 2001 (2531 individuals) and maximum during 2006 (16 610 individuals). In March 1998 the coasts of Laurie Island were surveyed by navigating inflatable boats near the shoreline; 18 haul-out places were identified. The big differences in peak numbers, as well as in the dates of peak events among years, suggest that local conditions could have an effect on the numbers of animals hauled out in a given year. It may therefore be difficult to predict trends from summer censuses in non-breeding places.
Keywords: Antarktis; pelsseler; zoologi

Entanglement of Antarctic fur seals at Bouvetøya, Southern Ocean - Greg Hofmeyr, G J; Bester, Marthán N; Kirkman, Steve P; Lydersen, Christian; Kovacs, Kit M (Marine Pollution Bulletin, 2006)
Keywords: Bouvetøya; forurensning; marin biologi; pelsseler; pinnipedier

Entanglement of Antarctic fur seals at Bouvetøya, Southern Ocean - Greg Hofmeyr, G.J.; Bester, Marthán N.; Kirkman, Steve P.; Lydersen, Christian; Kovacs, Kit M. (Marine Pollution Bulletin, 2006)
Entanglements of Antarctic fur seals Arctocephalus gazella were recorded during four summers from 1996 to 2002 at the subantarctic island, Bouvetøya. Rates of entanglement varied between 0.024% and 0.059%. These rates are low for a pinniped population and might be because of the geographic isolation of the haulout site. An apparent decrease in the levels of entanglement over the course of the study was likely due, at least in part, to the removal of entanglements by observers. At least two-thirds of entangling materials were generated by fishery sources. Since there is no known local source of anthropogenic marine pollution, seals become entangled either in waters distant from the island, or when materials drift into local waters. Significantly more subadults were found entangled than expected from the postulated population age class distribution.
Keywords: Bouvetøya; Sørishavet; marin biologi; marin forurensning; pelsseler; pinnipedier